2008
DOI: 10.1159/000187633
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic and Adipogenic Cell Fractions Isolated from Postnatal Mouse Calvaria

Abstract: The use of stem/progenitor cells represents a promising approach to treat craniofacial bone defects, but successful treatments will rely on the availability of cells that can be expanded in vitroand which will differentiate appropriately in vivo. The calvaria may represent a source of autologous cells for such purposes. We demonstrate expression of stem cell antigen-1 (Sca-1) in mouse calvaria. We isolated Sca-1+ and Sca-1 cells at high purity and tested the ability of these cells to dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 72 publications
3
11
0
Order By: Relevance
“…The present study was designed to determine the effects of BMP‐7 on the expression of lipogenic differentiation markers in FRC cells, which are more differentiated along the osteogenic pathway than are bone marrow cells. Previous studies have shown that FRC cells possess the potential for osteoblastogenesis and adipogenesis [Aubin, 1998; Bellows and Heersche, 2001; Hasegawa et al, 2008; Steenhuis et al, 2009; Yoshiko et al, 2010]. Our current results not only confirm that BMP‐7 stimulates expression of osteogenic differentiation markers in FRC cultures, but also demonstrate that it is capable of stimulating the expression of lipogenic markers.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The present study was designed to determine the effects of BMP‐7 on the expression of lipogenic differentiation markers in FRC cells, which are more differentiated along the osteogenic pathway than are bone marrow cells. Previous studies have shown that FRC cells possess the potential for osteoblastogenesis and adipogenesis [Aubin, 1998; Bellows and Heersche, 2001; Hasegawa et al, 2008; Steenhuis et al, 2009; Yoshiko et al, 2010]. Our current results not only confirm that BMP‐7 stimulates expression of osteogenic differentiation markers in FRC cultures, but also demonstrate that it is capable of stimulating the expression of lipogenic markers.…”
Section: Discussionsupporting
confidence: 86%
“…Rodent calvarial cells have been previously shown to have the potential for osteoblastogenesis and adipogenesis [Aubin, 1998; Bellows and Heersche, 2001; Hasegawa et al, 2008; Steenhuis et al, 2009; Yoshiko et al, 2010]. Moreover, we and others have shown that BMP‐7 stimulates the expression of characteristic osteogenic markers in several cell systems, including the FRC system [Asahina et al, 1996; Yeh et al, 1996; Chen et al, 2001; Kang et al, 2009].…”
Section: Resultsmentioning
confidence: 99%
“…These properties are also typical of MSC isolated from the adipose tissue [44], umbilical cord blood [53] and Wharton's jelly matrix [26], peripheral blood [47], hair follicles [67], periosteum [22], various synovial structures (their number increases at the early stages of osteoarthritis) [65], subchondral bone [43], calvarium bone [57], ligaments with tendons [10], nervous tissue [12], anulus fi brosus and nucleus pulposus of the intervertebral disk [51], and oral mucosa [63] and embryonic SC [28], including amniotic [60] and tooth germ cells [68].…”
Section: Characteristics and Sources Of Mscmentioning
confidence: 99%
“…By combining cell sorting with negative Sca‐1 selection, enriched stem and/or progenitor cell fractions can be obtained from neonatal or adult mice. Recent studies have shown that fetal and postnatal mouse calvaria can also provide a source of osteogenic stem/progenitor cells, which can be enriched by negative Sca‐1 immunomagnetic selection (Sca‐1 − ) . Sca‐1 − cell fractions can form bone in vitro or be loaded into absorbable gelatin sponges and then transplanted into mice to form bone in vivo …”
Section: Introductionmentioning
confidence: 99%
“…Sca‐1 expression is known to vary between different mouse strains and tissue types, and thus it would be necessary to evaluate their osteogenic potential and the quality of bone formed in vitro. Evaluation of osteogenic potential becomes apparent considering that Sca‐1 − and positive Sca‐1 (Sca‐1 + ) cell selection can also be used to enrich chondroprogenitor and adipoprogentior cells, respectively, and thus, if given the appropriate culture conditions, would form their corresponding cartilage and adipose tissue types . Current osteogenic assays include alkaline phosphatase (ALP) to detect osteoblastic differentiation and histochemical mineral stains, such as von Kossa and Alizarin Red, to quantify phosphate and calcium levels in vitro, respectively.…”
Section: Introductionmentioning
confidence: 99%